Chapter La competenza lessicale nei metodi d'insegnamento linguistico - maggini, massimo (Strumenti per la didattica e la ricerca, 2021)
The article analyzes the importance of the development of lexical competence within the various glottodidactic methods. In particular, it is highlighted how, at present, teaching vocabulary has definitively freed itself from a subordinate, almost accessory, position with respect to grammar teaching. The article then focuses on the role of the dictionary in learning vocabulary and on the necessary skills for its use. It is highlighted the lack, in Italian L2, of pedagogical dictionaries, i.e. simplified monolingual dictionaries specifically designed for a non-Italian speaking public. The article ends with the description of the most important corpora of Italian language, which could became useful operational tools in teaching vocabulary.